System for delivering microwave ablation to subcutaneous tumors in small-animals under high-field MRI thermometry guidance. (31st December 2022) - Sebek, Jan; Shrestha, Tej B.; Basel, Matthew T.; Chamani, Faraz; Zeinali, Nooshin; Mali, Ivina; Payne, Macy; Timmerman, Sarah A.; Faridi, Pegah; Pyle, Marla; O'Halloran, Martin; Dennedy, M. Conall; et al.
Abstract: Purpose: Bio-effects following thermal treatments are a function of the achieved temperature profile in tissue, which can be estimated across tumor volumes with real-time MRI thermometry (MRIT). Here, we report on expansion of a previously developed small-animal microwave hyperthermia system integrated with MRIT for delivering thermal ablation to subcutaneously implanted tumors in mice. Methods: Computational models were employed to assess suitability of the 2.45 GHz microwave applicators for delivering ablation to subcutaneous tumor targets in mice. Phantoms and ex-vivo tissues were heated to temperatures in the range 47–67 °C with custom-made microwave applicators for validating MRIT with the proton resonance frequency shift method against fiberoptic thermometry. HAC15 tumors implanted in nude mice ( n  = 6) were ablated in vivo and monitored with MRIT in multiple planes. One day post ablation, animals were euthanized, and excised tumors were processed for viability assessment. Results: Average absolute error between temperatures from fiberoptic sensors and MRIT was 0.6 °C across all ex-vivo ablations. During in-vivo experiments, tumors with volumes ranging between 5.4–35.9 mm 3 (mean 14.2 mm 3 ) were ablated (duration: 103–150 s) to achieve 55 °C at the tumor boundary. Thermal doses ≥240 CEM43 were achieved across 90.7–98.0% of tumor volumes for four cases. Ablations were incomplete for remaining cases, attributed to motion-affected thermometry. Thermal dose-based ablative tumor coverage agreed with viability assessment of excised tumors. Conclusions: We have developed a system for delivering microwave ablation to subcutaneous tumors in small animals under MRIT guidance and demonstrated its performance in - vivo .